A Comparison of Updating Frequency Between Web of Science and Current Contents Connect - Nancy J. Butkovich; Helen F. Smith; Claire E. Hoffman (Issues in Science and Technology Librarianship)
The Libraries at the Pennsylvania State University subscribe to the online databases Web of Science and Current Contents Connect. Concern was expressed regarding the great similarity in coverage between them. A comparison of title coverage found that Web of Science was more inclusive than Current Contents Connect across all disciplines. When updating frequency was compared, new science and social science journal issues appeared in both databases the same week approximately three quarters of the time. In the arts and humanities this is true only about half the time but these data are not as conclusive due to the small sample size. Each database has unique features. Web of Science has superior title coverage, while Current Contents Connect updates faster about 25% of the time. Unexpected significant problems were noted with updates to Current Contents Connect regarding timing of the updates and the definition of a "current week." The relative importance of the advantages and disadvantages of the two databases will vary depending on institutional needs.